Analysis of Tsunami Inundation due in Pangandaran Tsunami Earthquake in South Java Area Based on Finite Faults Solutions Model - Ramadhan Priadi; Dede Yunus; Berlian Yonanda; Relly Margiono (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2020)
On July 17, 2006 an earthquake with a magnitude of  7.7 triggered a tsunami that struck 500 km of the coast in the south of the island of Java. The tsunami generated is classified as an earthquake tsunami because the waves generated were quite large compared to the strength of the earthquake. The difference in the strength of the earthquake and the resulting tsunami requires a tsunami modeling study with an estimated fault area in addition to using aftershock and scaling law. The purpose of this study is to validate tsunamis that occur based on the estimation of the source mechanism and the area of earthquake faults. Determination of earthquake source mechanism parameters using the Teleseismic Body-Wave Inversion method that uses teleseismic waveforms with the distance recorded waveform from the source between  Whereas, tsunami modeling is carried out using the Community Model Interface for Tsunami (commit) method. Fault plane parameters that obtained were strike , dip , and rake  with dominant slip pointing up to north-north-west with a maximum value of 1.7 m. The fault plane is estimated to have a length of 280 km in the strike direction and a width of 102 km in the dip direction. From the results of the tsunami modeling, the maximum inundation area is 0.32 km2 in residential areas flanked by Pangandaran bays and the maximum run-up of 380.96 cm in Pasir Putih beach area. The tsunami modeling results in much smaller inundation and run-up from field observations, it was assumed that the fault plane segmentation had occurred due to the greater energy released than the one from the fault area, causing waves much larger than the modeling results.